Duloxetine-Induced Hypertension: A Case Report - Mermi, Osman; Atmaca, Murad (Turkiye Sinir ve Ruh Sagligi Dernegi, 2016)
Duloxetine, a serotonin-norepinephrine reuptake inhibitor, is used for diabetic neuropathic pain and fibromyalgia as well as major depressive disorder. Serotonin-norepinephrine reuptake inhibitors may lead to increased blood pressure via their noradrenergic effects in addition to their cardiovascular side effects. In this paper, we report a case with increased blood pressure after the initiation of duloxetine that recovered by discontinuation of the medication.
Keywords: Duloxetine; hypertension; side effect